Survivorship Bias and Mutual Fund Performance - Elton, Edwin J.; Gruber, Martin J.; Blake, Christopher R. (Review of Financial Studies, 1996)
[Mutual fund attrition can create problems for a researcher because funds that disappear tend to do so due to poor performance. In this article we estimate the size of the bias by tracking all funds that existed at the end of 1976. When a fund merges we calculate the return, taking into account the merger terms. This allows a precise estimate of survivorship bias. In addition, we examine characteristics of both mutual funds that merge and their partner funds. Estimates of survivorship bias over different horizons and using different models to evaluate performance are provided.]